Physical and Mechanical Properties of Oriented Flattened Bamboo Boards from Ater (Gigantochloa atter) and Betung (Dendrocalamus asper) Bamboos - Alfira Ramadhani Putri; Nur Alam; Ulfa Adzkia; Yusup Amin; I Wayan Darmawan; Lina Karlinasari (Department of Forestry, Faculty of Agriculture, University of Lampung, 2023)
Bamboo-based composite has been used widely for building components and furniture. Oriented flattened bamboo board (OFBB) is a composite board consisting of oriented structure sheets of flattening bamboo. This study aimed to analyze the physical and mechanical properties of the OFBB from ater (Gigantochloa atter) and betung (Dendrocalamus asper) bamboo. A three-layer flattened bamboo board using the isocyanate resin with a density target of 0.6 g/cm3 was applied. The characteristics of raw bamboo, the contact angle of OFBB, and board properties of density, moisture content, thickness swelling, and water absorption, as well as bending, internal bonding (IB), and compressive strength properties were determined to evaluate the quality of the OFBB. Based on the findings, the thin wall thickness of ater bamboo enhanced the physical and mechanical properties of the OFBB compared to the higher wall thickness of betung bamboo. Therefore, further development in bamboo composite products with those anatomical properties seems promising. The dimensional stability and bending properties of OFBB from ater bamboo met the quality of first grade of the Canadian Standard for OSB and waferboard, except for the IB strength. Keywords: Bamboo wall thickness, contact angle, Dendrocalamus asper, Gigantochloa atter, oriented flattened bamboo board